Overcoming indifference ten key challenges in today?s changing world : a survey of ideas and proposals for action on the threshold of the twenty-first century - Schwab,Klaus (New York New York University Press, 1995)
The end of the Cold War did not, as some might have hoped, simplify the issues facing world leaders. Civil war, famine, overpopulation, chronic unemployment, and an exploding refugee problem continue to plague the world economy, to the point where we begin to wonder whether national boundaries can contain such crises, or whether the challenges that face the world are beyond the reach of the leaders we have elected. Has the increasing disparity between the haves and the have nots, between the knows and don't knows led to an unbridgeable gap between rich and poor peoples and rich and poor countries?
Includes bibliographical references and index
Keywords: Economic policy